Traditional Chinese medicine and its active substances reduce vascular injury in diabetes via regulating autophagic activity - Gao, Yankui; Zhang, Lei; Zhang, Fei; Liu, Rong; Liu, Lei; Li, Xiaoyan; Zhu, Xiangdong; Liang, Yonglin (Frontiers in Pharmacology, 2024)
Due to its high prevalence, poor prognosis, and heavy burden on healthcare costs, diabetic vascular complications have become a significant public health issue. Currently, the molecular and pathophysiological mechanisms underlying diabetes-induced vascular complications remain incompletely understood. Autophagy, a highly conserved process of lysosomal degradation, maintains intracellular homeostasis and energy balance via removing protein aggregates, damaged organelles, and exogenous pathogens. Increasing evidence suggests that dysregulated autophagy may contribute to vascular abnormalities in various types of blood vessels, including both microvessels and large vessels, under diabetic conditions. Traditional Chinese medicine (TCM) possesses the characteristics of “multiple components, multiple targets and multiple pathways,” and its safety has been demonstrated, particularly with minimal toxicity in liver and kidney. Thus, TCM has gained increasing attention from researchers. Moreover, recent studies have indicated that Chinese herbal medicine and its active compounds can improve vascular damage in diabetes by regulating autophagy. Based on this background, this review summarizes the classification, occurrence process, and related molecular mechanisms of autophagy, with a focus on discussing the role of autophagy in diabetic vascular damage and the protective effects of TCM and its active compounds through the regulation of autophagy in diabetes. Moreover, we systematically elucidate the autophagic mechanisms by which TCM formulations, individual herbal extracts, and active compounds regulate diabetic vascular damage, thereby providing new candidate drugs for clinical treatment of vascular complications in diabetes. Therefore, further exploration of TCM and its active compounds with autophagy-regulating effects holds significant research value for achieving targeted therapeutic approaches for diabetic vascular complications.